Physical Activities and Sleeping Habits in Children and Adolescent During Pandemic Covid-19: A Systematic Review - Sarwoko, Sarwoko; Anggraeni, Titik; Bahri, Ahmad Syamsul (Journal of Maternal and Child Health, 2021)
Background:Lockdown during the COVID-19 pandemic can affect the behavior of daily habits among children and adolescents. This study aims to determine the effect of the COVID-19 pandemic lockdown on the physical activity and sleeping habits of children and adolescents.Subjects and Method:This study is a syste